Differential Regulation of Retinoblastoma Tumor Suppressor Protein by G(1) Cyclin-Dependent Kinase Complexes In Vivo - Ezhevsky, Sergei A. (American Society for Microbiology, 2001)
The retinoblastoma tumor suppressor protein (pRB) negatively regulates early-G(1) cell cycle progression, in part, by sequestering E2F transcription factors and repressing E2F-responsive genes. Although pRB is phosphorylated on up to 16 cyclin-dependent kinase (Cdk) sites by multiple G(1) cyclin-Cdk complexes, the active form(s) of pRB in vivo remains unknown. pRB is present as an unphosphorylated protein in G(0) quiescent cells and becomes hypophosphorylated (∼2 mol of PO(4) to 1 mol of pRB) in early G(1) and hyperphosphorylated (∼10 mol of PO(4) to 1 mol of pRB) in late G(1) phase. Here, we report that hypophosphorylated pRB, present in early G(1), represents the biologically active form of pRB in vivo that is assembled with E2Fs and E1A but that both unphosphorylated pRB in G(0) and hyperphosphorylated pRB in late G(1) fail to become assembled with E2Fs and E1A. Furthermore, using transducible dominant-negative TAT fusion proteins that differentially target cyclin D-Cdk4 or cyclin D-Cdk6 (cyclin D-Cdk4/6) and cyclin E-Cdk2 complexes, namely, TAT-p16 and TAT–dominant-negative Cdk2, respectively, we found that, in vivo, cyclin D-Cdk4/6 complexes hypophosphorylate pRB in early G(1) and that cyclin E-Cdk2 complexes inactivate pRB by hyperphosphorylation in late G(1). Moreover, we found that cycling human tumor cells expressing deregulated cyclin D-Cdk4/6 complexes, due to deletion of the p16(INK4a) gene, contained hypophosphorylated pRB that was bound to E2Fs in early G(1) and that E2F-responsive genes, including those for dihydrofolate reductase and cyclin E, were transcriptionally repressed. Thus, we conclude that, physiologically, pRB is differentially regulated by G(1) cyclin-Cdk complexes.